Analysis of the Needs for the Development of Moodle LMS-Based Interactive Learning Media in High School Physics Subjects - Chasani, Akrom; Yennita, Yennita (Jurnal Paedagogy, 2023)
The purpose of this research is to develop of Moodle LMS-Based interactive learning media at SMAIT Ulil Albab Batam Class XI in physics subject. The research used descriptive method which aims to capture and present the desired facts, realities, symptoms, and events appropriately. The research involved 48 SMAIT Ulil Albab Batam students and 31 Physics MGMP subject teachers in Batam City.Â  The questionnaire developed consisted of 18 question items for students and 19 question items for teachers based on four indicators then analyzed using descriptive statistical analysis techniques. The result showed that the average 3.40 for students and average 3.38 for teachers which is categorized as very high, it is necessary to develop interactive learning media as learning media.